Effect of injection strategy on the mixture formation and combustion process in a gasoline direct injection rotary engine. (15th November 2021) - Ji, Changwei; Chang, Ke; Wang, Shuofeng; Yang, Jinxin; Wang, Du; Meng, Hao; Wang, Huaiyu
Highlights: A gasoline direct injection rotary engine CFD model was established and validated. The coupled effects of injection position and injection angle were investigated. The mixture formation, combustion and emissions process were analyzed. Direct injection obtains higher indicated thermal efficiency than intake port injection. Upper injection position with 0° injection angle can reduce carbon-based emissions. Abstract: A computational fluid dynamics model was established and validated to numerically investigate the effects of different injection positions and injection angles on the mixture formation and combustion process in a gasoline direct injection rotary engine. The results show that as the injection position approaches the top dead center and the increasing injection angle, the rich zone of fuel changes from the rear to the front of the combustion chamber. The local equivalence ratio near the two spark plugs shows an increasing trend with the injection position upward and the increasing injection angle. Compared with the lower and middle injection positions, the upper injection positions can make fuel more concentrated near the leading spark plug and the trailing spark plug at ignition timing. The injection strategies corresponding to the upper injection position are conducive to complete combustion, in which the mass fraction of fuel burned all beyond 99%. Besides, with the increasing injection angle, the oil film formation position changes from the rotor recess to the middle cylinder block, which further affects the mixture formation and combustion process. Especially, the highest peak pressure is obtained at 0° injection angle corresponding to the upper injection position and is 12.39% higher than the in-cylinder peak pressure of intake port injection.